Unlocking the Power of Digital Games in Arabic Language Acquisition: A Meta-Analysis Across Educational Levels - Abdullah, Muhammad Yahya; Arrifqi, Nadia; Atulolon, Wardah Nailah El-Izzaah; Karim, Syauqi Miftahul; Gustian, Nabil (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study examines the effect of digital game-based learning (DGBL) on Arabic language acquisition and the moderating role of school level. Although digital games are increasingly used in education, their impact across grade levels remains underexplored. The study aims to measure the effect size of digital games on Arabic learning outcomes at different school levels and to determine whether these levels shape the effectiveness of DGBL. A meta-analysis of 19 studies was conducted to assess the impact. The results show that digital games significantly improve Arabic language acquisition, with the strongest effects at the Junior High School level, followed by University and Junior High School. Primary School learners show a smaller but still positive effect. These findings indicate that older learners gain more from digital games, likely due to greater cognitive maturity and familiarity with digital tools. This study contributes to research on digital learning by demonstrating how age and educational context influence DGBL outcomes. However, the study is limited by the small number of included studies and its focus on Arabic. Future research should explore other subjects and evaluate long-term outcomes of digital game-based learning in diverse settings.